Surface treatment film and method for producing the same and article

By forming a laminated structural surface treatment film with polymerization initiating groups on the surface of the substrate, the problem of detachment of the existing thick polymer brush under friction and solvent conditions is solved, and the durability and adhesion of the substrate surface are achieved.

CN116157422BActive Publication Date: 2025-03-25DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180057800.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-06
Filing Date
2021-08-03
Publication Date
2025-03-25
Estimated Expiration
2041-08-03

AI Technical Summary

Technical Problem

The existing thick polymer brushes are prone to detachment under conditions such as friction and solvent, and it is difficult to show low friction in the rough surface of the covering substrate, which increases costs.

Method used

The surface treatment film of the laminated structure is formed by providing a polymer layer with a polymerization initiating group on the surface of the substrate and forming another polymer layer thereon. The surface treatment film consists of a polymer layer with high mechanical strength and a polymer layer with specific properties.

Benefits of technology

It has achieved durability such as wear resistance, friction resistance, chemical resistance, heat resistance and solvent resistance to various substrate surfaces, and has excellent adhesion to the substrate surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116157422B_ABST
    Figure CN116157422B_ABST
Patent Text Reader

Abstract

Provided is a surface treatment film that can impart durability such as wear resistance, friction resistance, chemical resistance, heat resistance and solvent resistance to the surface of various substrates and has excellent adhesion to the surface of the substrate. A surface treatment film is provided on the surface of a substrate. It has a laminated structure comprising a polymer layer (i) and a polymer layer (ii), wherein the polymer layer (i) is arranged on the surface side of the substrate, and the polymer layer (ii) is arranged on the polymer layer (i), and the polymer layer (i) contains a first polymer, which is derived from a polymer containing a polymerization initiation group such as a polyester having a functional group represented by the general formula (1) (R1 represents a hydrogen atom, a methyl group, etc.; R2 represents a methyl group, etc.; X represents a chlorine atom, etc.; Y represents O or NH; * represents a bonding position) in the side chain, and the polymer layer (ii) contains a second polymer, which contains a structural unit derived from a monomer such as an aromatic vinyl monomer and is chain extended using the functional group represented by the general formula (1) as a polymerization initiation point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface treatment film provided on a substrate surface, a method for producing the same, and an article provided with the surface treatment film. Background Art

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group capable of adsorbing to or reacting with a substrate at its terminal is allowed to act on the substrate, thereby forming a polymer layer obtained by physical or chemical bonding on the surface of the substrate. In addition, a method is also known in which a monomer is polymerized using a polymerizable group imparted to the surface of the substrate as a starting point, thereby forming a polymer layer grafted from the surface of the substrate.

[0003] In recent years, the so-called "thick polymer brush" which is grafted onto a substrate at a high density using the living radical polymerization technology developed in the 1990s has been studied. In this thick polymer brush, polymer chains are grafted onto the substrate at a high density with a spacing of 1 to 4 nm. Using this thick polymer brush, the surface of the substrate can be modified to impart characteristics such as low friction, inhibition of protein adsorption, size exclusion properties, hydrophilicity, and water repellency (e.g., Patent Documents 1 and 2, Non-Patent Documents 1 to 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-133434

[0007] Patent Document 2: Japanese Patent Application Publication No. 2010-261001

[0008] Non-patent literature

[0009] Non-patent document 1: Adv. Polym. Sci., 2006, 197, 1-45

[0010] Non-patent document 2: J. Am. Chem. Soc., 2005, 127, 15843-15847

[0011] Non-patent document 3: Polym. Chem., 2012, 3, 148-153 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] Thick polymer brushes (hereinafter also referred to as "brushes") show low friction in the tribology field of lubrication, friction, and wear. However, sometimes the polymer layer of the brush is easily detached from the surface of the substrate depending on the lubricant or solvent used during friction. Thick polymer brushes are formed by polymerizing after forming a polymerization initiation group layer as a monomolecular film layer. However, since the bonding force and adhesion of the monomolecular film layer are weak, it is considered that the polymer layer is easily detached due to friction or solvents.

[0014] In addition, since the surface of the substrate forming the brush has unevenness, low friction may not be exhibited when the polymer layer of the brush does not completely cover the unevenness. In order to cover the roughness of the substrate surface, the substrate surface may be polished to make it smooth before forming the brush, but the step of polishing the substrate surface is increased, which is disadvantageous in terms of cost. It should be noted that the roughness of the substrate surface can be covered by forming a brush with a thicker film. However, in order to form a brush with a thicker film, special conditions and equipment are required, such as grafting to the substrate surface by active radical polymerization under high pressure conditions (e.g., 100 to 1,000 MPa). Therefore, it may not be easy to form a brush with a thicker film, and it is also easy to become disadvantageous in terms of cost.

[0015] The present invention is made in view of the problems of the prior art, and its subject is to provide a surface treatment film which can impart durability such as wear resistance, friction resistance, chemical resistance, heat resistance and solvent resistance to the surface of various substrates and has excellent adhesion to the surface of the substrate. In addition, the subject of the present invention is to provide a method for manufacturing the above-mentioned surface treatment film and an article having the above-mentioned surface treatment film.

[0016] Solutions for solving problems

[0017] As a result of research, the present inventors found that the above-mentioned problems can be solved by providing a polymer layer having a polymerization initiating group with high mechanical strength, excellent chemical resistance and solvent resistance on the surface of a substrate, and further providing another polymer layer by graft polymerization using the polymerization initiating group.

[0018] That is, according to the present invention, the following surface treatment films can be provided.

[0019] [1] A surface treatment film provided on the surface of a substrate, the surface treatment film having a laminated structure comprising a polymer layer (i) and a polymer layer (ii), the polymer layer (i) being arranged on the surface side of the substrate, the polymer layer (ii) being arranged on the polymer layer (i), the polymer layer (i) containing a first polymer, the first polymer being derived from a polymer containing a polymerization initiating group, the polymer containing a polymerization initiating group having a functional group represented by the following general formula (1) functioning as a polymerization initiating group in a side chain, and being selected from the group consisting of polyester, polyurethane, polyamide, poly The present invention relates to a second polymer comprising at least one of the group consisting of an imide and an epoxy resin, and in the polymer containing a polymerization initiating group, the content of the functional group represented by the general formula (1) is 0.5 mmol / g or more, the film thickness of the polymer layer (ii) is 200 nm or more, and the polymer layer (ii) contains a second polymer, wherein the second polymer comprises a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer and a (meth)acrylamide monomer, and the chain is extended using the functional group represented by the following general formula (1) as a polymerization initiating point.

[0020]

[0021] (In the above general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; Y represents O or NH; * represents a bonding position)

[0022] [2] The surface treatment film according to [1] above, wherein the polymer layer (i) has a three-dimensional network structure.

[0023] [3] The surface treatment film according to [1] or [2], wherein the polymer layer (i) has a thickness of 500 nm or more.

[0024] [4] A surface treatment film according to any one of [1] to [3] above, wherein the polymer containing a polymerization initiating group has a functional group represented by the general formula (1) in a side chain and is selected from at least one of the group consisting of polyester, polyurethane, polyimide and epoxy resin.

[0025] [5] The surface treatment film according to any one of [1] to [4], wherein the polymer layer (ii) contains a solvent and is swollen.

[0026] [6] The surface treatment film according to any one of [1] to [5], which is provided on the surface of the substrate (excluding porous substrates).

[0027] [7] The surface-treated film according to any one of [1] to [6], wherein the second polymer has a polystyrene-equivalent number average molecular weight of 100,000 or more as measured by gel permeation chromatography.

[0028] Furthermore, according to the present invention, there is provided a method for producing a surface-treated film described below.

[0029] [8] A method for producing a surface treatment film, which is the method for producing a surface treatment film according to any one of the above [1] to [7], comprising the following steps: a step of forming a polymer layer (iii) on the surface of the above substrate, wherein the polymer layer (iii) contains the above polymer containing a polymerization initiating group; and a step of polymerizing one or more monomers selected from the group consisting of aromatic vinyl monomers, (meth)acrylate monomers and (meth)acrylamide monomers in the presence of the above polymer layer (iii) to form a laminated structure comprising the above polymer layer (i) and the above polymer layer (ii), wherein the polymer layer (i) contains the above first polymer derived from the above polymer containing a polymerization initiating group, and the polymer layer (ii) is arranged on the above polymer layer (i) and contains the above second polymer containing a structural unit derived from the above monomer.

[0030] [9] The method for producing a surface-treated film according to [8], wherein the polymer layer (iii) is formed by coating the polymer containing a polymerization initiating group on the surface of the substrate.

[0031]

[10] A method for producing a surface treatment film according to the above-mentioned [8], wherein after at least one polymer having a hydroxyl group or an amino group in a side chain and selected from the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin is coated on the surface of the above-mentioned substrate, it is reacted with a compound represented by the following general formula (2) to form the above-mentioned polymer layer (iii).

[0032]

[0033] (In the above general formula (2), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; and Z represents a chlorine atom or a bromine atom.)

[0034]

[11] The method for producing a surface-treated film according to any one of [8] to

[10] , wherein the monomer is subjected to surface-initiated living radical polymerization in the presence of the polymer layer (iii).

[0035]

[12] The method for producing a surface treatment film according to any one of [8] to

[11] above, wherein the monomer is polymerized under a pressure condition of 10 to 1,000 MPa.

[0036]

[13] The method for producing a surface treatment film according to any one of [8] to

[12] above, wherein the monomer is polymerized under a pressure condition of 100 to 1,000 MPa.

[0037] Furthermore, according to the present invention, the following articles are provided.

[0038]

[14] An article comprising a substrate and the surface treatment film according to any one of [1] to [7] provided on a surface of the substrate.

[0039] Effects of the Invention

[0040] According to the present invention, a surface treatment film having excellent adhesion to the surface of a substrate and capable of imparting durability such as wear resistance, friction resistance, chemical resistance, heat resistance and solvent resistance to the surface of various substrates can be provided. In addition, according to the present invention, a method for manufacturing the surface treatment film and an article having the surface treatment film can be provided. DETAILED DESCRIPTION

[0041] <Surface treatment film and method for producing the same>

[0042] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The surface treatment film of the present invention is a film disposed on the surface of a substrate, and has a laminated structure comprising a polymer layer (i) and a polymer layer (ii), wherein the polymer layer (i) is disposed on the surface side of the substrate, and the polymer layer (ii) is formed on the polymer layer (i). The polymer layer (i) contains a first polymer, the first polymer being derived from a polymer containing a polymerization initiating group, the polymer containing a polymerization initiating group having a functional group represented by the general formula (1) in a side chain that functions as a polymerization initiating group, and being selected from at least one of the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin. In the polymer containing the polymerization initiating group, the content of the functional group represented by the general formula (1) is 0.5 mmol / g or more. Furthermore, the polymer layer (ii) contains a second polymer, the second polymer comprising a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth) acrylate monomer and a (meth) acrylamide monomer, and the chain is extended using the functional group represented by the general formula (1) as a polymerization initiating point. Hereinafter, the surface treatment film of the present invention will be described in detail.

[0043] (Polymer layer (i))

[0044] The surface treatment film has a laminated structure including a polymer layer (i) and a polymer layer (ii). The polymer layer (i) is a layer disposed on the surface side of the substrate, and is a layer containing a first polymer, the first polymer being derived from a polymer containing a polymerization initiating group (hereinafter also referred to as an "initiating group polymer"), the initiating group polymer having a functional group represented by the following general formula (1) in a side chain that functions as a polymerization initiating group, and at least one selected from the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin, and the polymer layer (i) is preferably a layer substantially formed by the first polymer.

[0045]

[0046] (In the above general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; Y represents O or NH; and * represents a bonding position.)

[0047] For example, a component (coating liquid) containing a polymer containing a polymerization initiating group having a functional group represented by the general formula (1) in a side chain can be applied to the surface of a substrate, dried, and cured, thereby forming a polymer layer (polymer layer (iii)) containing a polymer containing a polymerization initiating group. Furthermore, if one or more monomers selected from the group consisting of aromatic vinyl monomers, (meth)acrylate monomers, and (meth)acrylamide monomers are polymerized by a prescribed method in the presence of the polymer layer (iii), the functional group represented by the general formula (1) is used as a polymerization initiation point, and the second polymer undergoes chain extension. Thus, a polymer layer (i) containing the first polymer is formed on the surface of the substrate, and a polymer layer (ii) containing the second polymer, preferably substantially formed by the second polymer, is arranged on the polymer layer (i), and a surface treatment film can be obtained.

[0048] In the general formula (1), the halogen atom such as the chlorine atom represented by X is released in the form of a halogen free radical due to the action of light, heat, free radicals, etc., to generate a tertiary carbon free radical or a quaternary carbon free radical. The generated tertiary carbon free radical or quaternary carbon free radical attacks the aforementioned monomer having a group capable of free radical polymerization to react, and the second polymer undergoes chain extension.

[0049] The polymer containing a polymerization initiating group is a non-olefinic polymer such as polyester, polyurethane, polyamide, polyimide and epoxy resin having a functional group represented by the general formula (1) in the side chain and functioning as a polymerization initiating group. The non-olefinic polymer having the functional group represented by the general formula (1) in the side chain can be obtained using, for example, a polymerization component containing a monomer having the functional group represented by the general formula (1). In addition, the monomer having the functional group represented by the general formula (1) can be obtained by, for example, reacting a compound containing a polymerization initiating group such as a compound represented by the following general formula (3), an acid anhydride or an acid halide thereof with a compound having a hydroxyl group, an amino group, an epoxy group or an isocyanate group.

[0050]

[0051] (In the above general formula (3), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; and X represents a chlorine atom, a bromine atom or an iodine atom.)

[0052] A compound containing a polymerization initiating group, such as a compound represented by the general formula (3), is reacted with glycidol, an epoxy group of a compound having two or more epoxy groups, or an amino group of a compound having an amino group and a hydroxyl group, such as 2-aminopropylene glycol, to obtain a diol component. Furthermore, polyester can be obtained by condensing the obtained diol component with a dicarboxylic acid or other diols. In addition, polyurethane can be obtained by reacting a compound containing a polymerization initiating group, such as a compound represented by the general formula (3), with a diisocyanate, other diols, diamines, etc.

[0053] A compound containing a polymerization initiating group, such as a compound represented by the general formula (3), is reacted with a compound having three or more amino groups to obtain a diamine component. Furthermore, by reacting the obtained diamine component with a dicarboxylic acid or an acid anhydride, polyamides and polyimides can be obtained. In addition, a urethane prepolymer prepared by using isocyanate and diol is reacted with the above-mentioned diamine component as a chain extender to obtain a polyurethane. Furthermore, by reacting the above-mentioned diamine component with a compound having two or more epoxy groups, an epoxy resin can be obtained. The type of polymer containing a polymerization initiating group (first polymer) can be appropriately selected in consideration of the adhesion to the substrate, etc. In addition, by reacting the above-mentioned non-olefinic polymer having a hydroxyl group or an amino group in the side chain with a compound containing a polymerization initiating group, such as a compound represented by the general formula (3), a polymer containing a polymerization initiating group can also be obtained.

[0054] As compounds such as the compounds represented by the general formula (3) containing polymerization initiating groups, for example, 2-chloropropionic acid, 2-chlorobutyric acid, 2-chloroisobutyric acid, 2-chlorovaleric acid, 2-bromopropionic acid, 2-bromobutyric acid, 2-bromoisobutyric acid, 2-bromovaleric acid, α-bromophenylacetic acid, α-bromo-4-chloroacetic acid and other halogen-substituted carboxylic acid compounds, their anhydrides and their acid halides, etc. As compounds such as the compounds represented by the general formula (3) containing polymerization initiating groups, 2-bromoisobutyric acid and its derivatives are preferred. These compounds are easily available as commercial products and the halogen atoms are easily separated. In addition, the generated free radicals are relatively stable, so side reactions can be suppressed.

[0055] A non-olefinic polymer (polymer containing a polymerization initiating group) having a functional group shown in the general formula (1) in a side chain is dissolved in a solvent such as an organic solvent to prepare a solution (coating solution). Furthermore, by applying the prepared coating solution to a substrate and then drying it, a polymer layer (iii) containing a polymer containing a polymerization initiating group can be formed on the surface of the substrate. It is preferred to use a polymer containing a polymerization initiating group having a reactive group with active hydrogen such as a hydroxyl group, a carboxyl group, an amino group, an alkoxysilyl group, and reacting with a crosslinking agent or a curing agent having a group that can react with these reactive groups to form a polymer layer (iii) having a three-dimensional network structure (crosslinked structure). Thus, a polymer layer (i) having a three-dimensional network structure and various characteristics such as mechanical strength, adhesion, chemical resistance, flexibility and friction resistance can be further improved, and a surface treatment film having such a polymer layer (i) can be formed.

[0056] In the case where the reactive group is a hydroxyl group, by reacting the cross-linking agent with isocyanate group, blocked isocyanate group, a cross-linked structure (three-dimensional network structure) with carbamate bond can be formed. In the case where the reactive group is a carboxyl group, cross-linking agents such as carbodiimide cross-linking agents, epoxy cross-linking agents, melamine cross-linking agents and oxazoline cross-linking agents can be reacted. In the case where the reactive group is an amino group, cross-linking agents such as isocyanate cross-linking agents, epoxy cross-linking agents and melamine cross-linking agents can be reacted. In the case where the reactive group is an alkoxysilyl group, self-reaction can occur, and monomers such as tetraethoxysilane can also be used in combination.

[0057] Examples of methods for applying the coating liquid to the surface of the substrate include screen printing, dip coating, inkjet, spin coating, plate coating, rod coating, slit coating, edge casting, spray coating, roll coating, curtain coating, gravure printing, flexographic printing, gravure offset printing, etc. Among them, the inkjet method is preferred, which can be applied (printed) into any shape according to real-time demand.

[0058] In addition, after coating the surface of the substrate with at least one polymer (non-olefinic polymer) having a hydroxyl group or an amino group in the side chain and selected from the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin, and then reacting it with the compound represented by the following general formula (2), the polymer layer (iii) can also be formed.

[0059]

[0060] (In the above general formula (2), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; and Z represents a chlorine atom or a bromine atom.)

[0061] In order to promote the reaction between the non-olefinic polymer having a hydroxyl group or an amino group in the side chain and the compound represented by the general formula (2), it is preferred to use an amine compound such as pyridine or triethylamine. If the hydroxyl group or the amino group of the non-olefinic polymer is reacted with the compound represented by the general formula (2) in the presence of an amine compound, dehydrohalogenation can be promoted.

[0062] In the polymer containing the polymerization initiating group, the content of the functional group represented by the general formula (1) is 0.5 mmol / g or more, preferably 1 mmol / g or more, more preferably 1.2 mmol / g or more and 100 mmol / g or less. If the content of the functional group represented by the general formula (1) that functions as a polymerization initiating group is less than 0.5 mmol / g, the surface occupancy and grafting rate of the formed polymer layer (ii) are insufficient. Therefore, it is difficult to fully exert the properties derived from the polymer layer (ii), such as low friction, lubricity, liquid retention, high elasticity, size exclusion effect and supercooling effect.

[0063] The film thickness of the polymer layer (i) is preferably 100 nm or more, more preferably 150 nm or more, and particularly preferably 500 nm or more and 10,000 nm or less. By setting the film thickness of the polymer layer (i) to 100 nm or more, the adhesion on the substrate surface is further improved, and the substrate surface can be modified more effectively. The film thickness of each polymer layer (polymer layer (i) to (iii)) and the surface treatment film can be measured by, for example, a measurement method using a precision instrument such as an atomic force microscope and an ellipsometer, a measurement method based on observation using an electron microscope, a measurement method using a film thickness measuring instrument, etc.

[0064] (Polymer layer (ii))

[0065] In the presence of the polymer layer (iii) disposed on the surface of the substrate, a specific monomer is polymerized. Thus, the second polymer is chain extended using the functional group represented by the general formula (1) as a polymerization initiation point, and a surface treatment film having a laminated structure including a polymer layer (i) and a polymer layer (ii) can be obtained, wherein the polymer layer (i) is disposed on the surface side of the substrate and the polymer layer (ii) is disposed on the polymer layer (i).

[0066] As the specific monomer, one or more monomers selected from the group consisting of aromatic vinyl monomers, (meth)acrylate monomers and (meth)acrylamide monomers are used. Among them, (meth)acrylate monomers are preferred because of their high polymerization rate and mild polymerization conditions.

[0067] Examples of the aromatic vinyl monomer include styrene, vinyltoluene, vinylhydroxybenzene, chloromethylstyrene, vinylnaphthalene, vinylbiphenyl, vinylethylbenzene, vinyldimethylbenzene, and α-methylstyrene.

[0068] Examples of the (meth)acrylate monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, 2-methylpropane (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate, and octadecyl (meth)acrylate. aliphatic alkyl (meth)acrylates, alicyclic alkyl (meth)acrylates, aromatic alkyl (meth)acrylates, and the like, such as behenyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl methyl (meth)acrylate, isobornyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, cyclodecyl methyl (meth)acrylate, benzyl (meth)acrylate, tert-butylbenzotriazolephenylethyl (meth)acrylate, phenyl (meth)acrylate, naphthyl (meth)acrylate, and allyl (meth)acrylate.

[0069] As the (meth)acrylate monomer, a (meth)acrylate compound containing a hydroxyl group, a diol group, an acid group (carboxyl group, sulfonic acid group, phosphoric acid group, etc.), an oxygen atom, an amino group, a nitrogen atom, etc. may be used.

[0070] Examples of the (meth)acrylamide monomer include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and (meth)acryloylmorpholine.

[0071] By using an organic solvent, an additive, a catalyst, etc., a surface-initiated free radical polymerization or a surface-initiated active free radical polymerization is carried out under pressure conditions of normal pressure to 1,000 MPa, preferably under pressure conditions of 100 MPa or more, so that a second polymer can be formed. From the aspect of initiating the polymerization by a polymerization initiating group having a halogen atom, it is preferred to polymerize the monomer by atom transfer radical polymerization using a metal complex that is known in the art. As metal complexes, complexes of copper chloride, copper bromide and polyamines such as dinonyl bipyridine, tris(dimethylaminoethyl)amine, and pentamethyldiethylenetriamine; dichlorotris(triphenylphosphine)ruthenium, etc. can be listed. Atom transfer radical polymerization can be bulk polymerization or solution polymerization using an organic solvent, etc. As an organic solvent, a hydrocarbon solvent, an ester solvent, a glycol solvent, an ether solvent, an amide solvent, an alcohol solvent, a sulfoxide solvent, a urea solvent, an ionic liquid, etc. can be used.

[0072] In atom transfer radical polymerization, due to the use of heavy metals, it is necessary to consider coloring and the burden on the environment, and it is necessary to remove it from the reaction system. Therefore, it is preferred to polymerize in the presence of a general organic compound that does not use heavy metals. Specifically, it is preferred to carry out surface-initiated radical polymerization or surface-initiated active radical polymerization in the presence of at least one salt selected from the group consisting of halogenated quaternary ammonium salts, halogenated quaternary phosphonium salts and halogenated alkali metal salts. Thus, commercially available and inexpensive organic materials and inorganic salts can be used for polymerization. In addition, since it is not necessary to remove the metal, the burden on the environment can be reduced and the process can be simplified.

[0073] X (halogen) in the general formula (1) is released as a free radical, and polymerization is carried out by inserting a monomer into a carbon radical generated simultaneously with the release of X. At this time, by making the above-mentioned specific salt coexist, the halogen free radical is removed or halogen exchange occurs, and the monomer is polymerized from the generated carbon radical to form a second polymer.

[0074] Examples of the halogenated quaternary ammonium salt include benzyltrimethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetraoctylammonium iodide, nonylpyridinium chloride, and choline chloride. Examples of the halogenated quaternary phosphonium salt include tetraphenylphosphonium chloride, methyltributylphosphonium bromide, and tetrabutylphosphonium iodide. Examples of the halogenated alkali metal salt include lithium bromide and potassium iodide.

[0075] As the salt, an iodide salt is preferably used. By using an iodide salt, living radical polymerization is performed, and a second polymer with a narrower molecular weight distribution can be obtained. In addition, it is preferred to use a salt that can be dissolved in a polymerization solution of a quaternary ammonium iodide salt, a quaternary phosphonium iodide salt, and an alkali metal iodide salt, and it is further preferred to use a quaternary ammonium iodide salt. As the quaternary ammonium iodide salt, benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dodecyltrimethylammonium iodide, octadecyltrimethylammonium iodide, tri-octadecylmethylammonium iodide, etc. can be listed.

[0076] From the viewpoint of improving the activity and obtaining a denser and higher molecular weight second polymer, the amount of the salt relative to the polymerization initiating group is preferably an equivalent mole or more, more preferably 10 times the mole or more, and can be 100 times the mole or more.

[0077] In the method using the quaternary salt or halide salt, the polymerization conditions are not particularly limited. It is carried out under the conditions known in the art. The temperature is preferably above 60°C, and as the solvent, an organic solvent is preferably used. As the solvent, a known solvent can be used, and there is no particular limitation. The solvent can use the aforementioned known organic solvent, and preferably a solvent that dissolves the salt, preferably an organic solvent with high polarity such as an alcohol, a diol, an amide, a urea, a sulfoxide, an ionic liquid, etc.

[0078] The polymerization is carried out under a pressure of normal pressure to 1,000 MPa, preferably 10 to 1,000 MPa, more preferably 100 to 1,000 MPa, further preferably 200 to 800 MPa, and particularly preferably 300 to 600 MPa. Specifically, the polymerization is carried out while uniformly applying pressure to the entire polymerization container containing the monomer and the substrate with the aid of a medium such as water. By carrying out the free radical polymerization under pressure, the termination reaction can be suppressed, and a second polymer with a higher molecular weight can be formed.

[0079] It is difficult to prepare a container or device that can withstand a pressure exceeding 1,000 MPa, which is not practical. As the molecular weight of the second polymer formed increases, the thickness of the polymer layer (ii) becomes thicker. By increasing the thickness of the polymer layer (ii), the surface of the substrate can be modified to exhibit properties that have not been seen so far. The thickness of the polymer layer (ii) can be set, for example, to a few nm to a few μm, preferably to 100 nm or more, more preferably to 200 nm or more, and particularly preferably to 1,000 nm or more and 10,000 nm or less.

[0080] As a polymerization container, it is preferred to use a container that can be sealed and withstand high pressure. In addition, since it is necessary to conduct pressure to the inside of the container, it is preferred to use a container having a soft part made of plastic, a telescopic part, and other parts that are deformed by pressure. Specifically, various containers such as polyethylene bottles, plastic bottles, retort bags, and blister containers can be used. In addition, it is preferred to use a container formed of a raw material that is not easily deformed at the temperature during polymerization and has heat resistance. Furthermore, it is preferred to use a container formed of a raw material that is not easily corroded by polymerization solvents, etc., and has characteristics such as chemical resistance and solvent resistance. As raw materials constituting the polymerization container, for example, polyolefin resins, fluorine resins, polyester resins, polyamide resins, engineering plastics, etc. can be listed. In addition, it is preferred to prevent gas from entering the polymerization container as much as possible during polymerization. For example, it is preferred to put the polymerization solution into more than 90% of the capacity of the polymerization container.

[0081] In the above, by putting a polymerization solution of a substrate, a monomer, a catalyst, etc. into a polymerization container, applying an external pressure of normal pressure or above normal pressure and below 1,000 MPa, preferably heating it to polymerize it, so that the second polymer is extended from the polymerization initiation point of the polymer layer (iii), and the surface of the substrate can be modified. The surface of the substrate can be modified to any property according to the type of monomer used, etc. For example, by using a fluorine-based monomer, a polymer layer (ii) with low surface tension that easily repels water and oil can be formed. By using monomers having a polyethylene glycol group, a carboxyl group, etc., a hydrophilic polymer layer (ii) can be formed in which the water vapor in contact immediately forms water droplets and is not easy to become blurred. Furthermore, a biocompatible substrate to which proteins, etc. are not easy to adhere can also be manufactured. In addition, the formed polymer layer (ii) can be swollen using a lubricating oil, etc. to form a lubricating film, thereby forming an extremely low friction polymer layer.

[0082] It is not easy to verify the molecular weight of the second polymer constituting the formed polymer layer (ii). Therefore, it is preferred to carry out surface-initiated free radical polymerization or surface-initiated active free radical polymerization in the coexistence of an initiating group monomer having the same initiating group as the polymerization initiating group. Thus, a free polymer not contained in the polymer layer (ii) is formed. In addition, by measuring the molecular weight of the formed free polymer according to conventional methods, the molecular weight of the second polymer constituting the polymer layer (ii) can be inferred. The polystyrene-converted number average molecular weight (Mn) of the formed free polymer measured by gel permeation chromatography (GPC) is generally 1,000 to 10,000,000, preferably 100,000 or more.

[0083] As the initiator monomer, a compound having the same group as the polymerization initiator is used. Specifically, compounds represented by the following formulae (4) to (6) can be used as the initiator monomer.

[0084]

[0085] The polymer layer (ii) preferably contains a solvent such as water, an organic solvent or a mixed solvent thereof and swells. The film thickness of the polymer layer (ii) can be increased by swelling it with a solvent. Furthermore, the swollen polymer layer (ii) shows specific properties such as strong resistance and low friction for compression, so it is preferred. The polymer layer (ii) can be swollen by, for example, immersing a substrate having a surface treatment film formed on its surface in a solvent.

[0086] <Items>

[0087] The article of the present invention comprises a substrate and the aforementioned surface treatment film disposed on the surface of the substrate. The type of substrate is not particularly limited, and natural objects, artificial objects, inorganic components, and organic components can all be used. Among them, it is preferred to use a substrate that can withstand a polymerization solution. As specific examples of the substrate, mechanical parts, films, fibers, sheets, etc. such as metals, metal oxides, metal nitrides, metal carbides, ceramics, wood, silicon compounds, thermoplastic resins, thermosetting resins, cellulose, and glass can be listed.

[0088] The substrate may be subjected to a surface treatment. Examples of the surface treatment include inorganic treatments such as silane coupling treatment, silica coating treatment, and silica alumina treatment; and treatments such as cleaning, activation, and imparting surface treatment functional groups such as plasma treatment, ultraviolet irradiation treatment, ozone oxidation treatment, radiation treatment, X-ray treatment, electron beam treatment, and laser treatment.

[0089] The film thickness of the polymer layer (i) is preferably thicker than the maximum height Rz of the surface roughness of the substrate surface. The surface of a general substrate usually produces concavities and convexities in the nanometer to micrometer units. If the polymer layer (i) is too thin, it is sometimes not enough to cover the concavities and convexities and expose the convex portions. In addition, even if the convex portions are barely covered, the surface shape of the polymer layer (i) will also reflect the concavities and convexities of the substrate, and the surface of the polymer layer (ii) formed thereon is also prone to concavities and convexities. Therefore, by making the film thickness of the polymer layer (i) thicker than the maximum height Rz of the surface roughness of the substrate surface, the entire surface of the substrate can be evenly covered and made smooth. In addition, a smoother polymer layer (ii) can be formed on the entire surface of the polymer layer (i).

[0090] By providing a surface treatment film having a laminated structure including a polymer layer (i) that is closely attached to the substrate and imparts mechanical strength and a polymer layer (ii) that exhibits specific properties on the substrate surface, the article of the present invention that is imparted with performance as a component or has improved performance can be produced. The article of the present invention is suitable as an article used in various fields such as medical components, electronic materials, display materials, semiconductor materials, mechanical components, sliding components, battery materials, etc.

[0091] Example

[0092] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that "parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0093] <Synthesis of Polymer Containing Polymerization Initiating Group>

[0094] (Synthesis Example 1: Initiator Group Polymer 1)

[0095] Into a reaction vessel equipped with a stirring device, stirring blades, a thermometer, a cooling tube, a gas introduction device and a dropping device, 69.4 parts of bisphenol A epoxy resin (trade name "jER-1001", manufactured by Mitsubishi Chemical Corporation, molecular weight of about 900), 304.0 parts of 3-methoxy-N,N-dimethylpropionamide (manufactured by KJ Chemical Co., Ltd.) (KJCMPA) and 17.8 parts of pyridine were added and stirred to dissolve. While cooling the reaction vessel with an ice bath, 43.1 parts of 2-bromoisobutyric acid bromide (BiBB) were added dropwise over 2 hours. After stirring at room temperature for 3 hours, 43.1 parts of methanol were added to stop the reaction.

[0096] 1,250 parts of water and 1,250 parts of methanol were put into a beaker, and the reaction solution was slowly added while vigorously stirring with a disperser. After filtering the precipitate, it was washed with a mixed solvent of water / methanol = 1:1 (mass ratio). Using an air-suppressed dryer, it was dried at 100°C for 24 hours to obtain 95.2 parts of the initiator polymer-1. The obtained initiator polymer-1 was analyzed by infrared spectroscopy (IR) using an infrared spectrophotometer (trade name "NICOLET 6700", manufactured by Thermo Scientific). As a result, at 1,735cm -1 Absorption derived from the ester bond was observed near . In addition, proton nuclear magnetic resonance spectroscopy (NMR) using a nuclear magnetic resonance apparatus (trade name "JNM-ECZR 400 MHz", manufactured by JEOL Ltd.) 1 H NMR) was used to analyze the obtained initiator polymer-1. As a result, a peak of a methyl group adjacent to the carbon atom bonded with a bromine group was observed at around δ = 1.9 ppm. Based on the above analysis results, it can be confirmed that the functional group represented by the general formula (1) is introduced into the initiator polymer-1. It should be noted that the content of the functional group represented by the general formula (1) in the initiator polymer-1 is 1.6 mmol / g.

[0097] (Synthesis Example 2: Initiator Group Polymer-2)

[0098] The same operation as in Synthesis Example 1 was performed except that 53.2 parts of bisphenol F epoxy resin (trade name "jER-4010P", manufactured by Mitsubishi Chemical Corporation, molecular weight of about 8,400) was used instead of bisphenol A epoxy resin, and 313.5 parts of KJCMPA, 23.7 parts of pyridine and 57.5 parts of BiBB were used to obtain 85.2 parts of initiator polymer-2. In initiator polymer-2, the content of the functional group represented by general formula (1) was 2.4 mmol / g.

[0099] (Synthesis Example 3: Initiator Group Polymer-3)

[0100] 27.5 parts of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (BIS-AP-AF) and 175.5 parts of dimethylacetamide (DMAc) were added to a reaction container and stirred at room temperature to dissolve. 16.4 parts of pyromellitic anhydride (PMDA) were added little by little and dissolved, and then stirred at room temperature for 12 hours to obtain an amic acid (polymer) solution. The number average molecular weight (Mn) of the polymer measured in terms of polystyrene was 18,500, and the molecular weight distribution (Mw / Mn, dispersion degree PDI) was 2.68 using a gel permeation chromatography (GPC) apparatus (trade name "GPC-101", manufactured by Shoko Scientific Co., Ltd., column: KD-806M×2, developing solvent: 30 mmol / L lithium bromide + 30 mmol / L phosphoric acid added dimethylformamide (DMF)). The polymer solution was spread in a vat, heated in an oven at 150°C for 2 hours under reduced pressure to distill off the solvent, and then heated at 200°C for 10 hours to close the ring. The obtained product was dissolved in 175.5 parts of N-methyl-2-pyrrolidone (NMP) and put into a reaction container. After adding 11.1 parts of pyridine, 25.9 parts of BiBB were added dropwise under ice cooling. After stirring at room temperature for 3 hours, 25.9 parts of methanol were added to stop the reaction.

[0101] 1,250 parts of water and 1,250 parts of methanol were added to a beaker, and the reaction solution was slowly added while vigorously stirring with a disperser. After filtering the precipitate, it was washed with a mixed solvent of water / methanol = 1:1 (mass ratio). Using a forced air dryer, it was dried at 100°C for 24 hours to obtain 44.6 parts of initiator polymer-3. In the initiator polymer-3, the content of the functional group represented by the general formula (1) was 1.8 mmol / g.

[0102] (Synthesis Example 4: Hydroxyl-containing polymer-1, initiator group polymer-4)

[0103] 200 parts of bisphenol A epoxy resin (trade name "Epotohto YD-128", manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., molecular weight of about 375), 40 parts of sodium iodide and 150 parts of N-methyl-2-pyrrolidone were placed in a reaction vessel. Carbon dioxide was continuously blown in while stirring the contents, and the mixture was reacted at 100° C. for 10 hours. 600 parts of water was added, and the precipitate was filtered. The precipitate obtained by using toluene was recrystallized to obtain 102 parts of white powder.

[0104] 100 parts of the obtained white powder, 27.2 parts of hexamethylenediamine and 190.8 parts of DMF were placed in a reaction container and reacted at 80°C for 24 hours to obtain a hydroxyl-containing polymer-1. A portion of the reaction solution was sampled and analyzed by IR, confirming that 1,800 cm -1 The peak derived from the carbonyl group of the nearby carbonate group disappears. The polystyrene-equivalent number average molecular weight (Mn) of the hydroxyl-containing polymer-1 measured using a GPC apparatus (developing solvent: DMF) was 11,200, and the molecular weight distribution (Mw / Mn, dispersion index PDI) was 2.87.

[0105] After adding 8.3 parts of pyridine to the reaction solution (solution of polymer-1 containing hydroxyl groups), 21.8 parts of BiBB were added dropwise over 2 hours under ice cooling. After stirring at room temperature for 3 hours, 21.8 parts of methanol were added to stop the reaction. 1,250 parts of water and 1,250 parts of methanol were put into a beaker, and the reaction solution was slowly added while vigorously stirring with a disperser. After filtering the precipitate, it was washed with a mixed solvent of water / methanol = 1:1 (mass ratio). Using a forced air dryer, it was dried at 100°C for 24 hours to obtain 140.6 parts of initiator polymer-4. In the initiator polymer-4, the content of the functional group represented by the general formula (1) is 0.7 mmol / g.

[0106] (Comparative Synthesis Example 1: Comparative Initiator Polymer-1)

[0107] Except that the amount of BiBB was changed to 4.3 parts, the same operation as in Synthesis Example 1 was carried out to obtain 72.7 parts of Comparative Initiator Polymer-1. The content of the functional group represented by the general formula (1) in Comparative Initiator Polymer-1 was 0.3 mmol / g.

[0108] <Manufacturing of coating liquid (1)>

[0109] (Production Example 1: COT-1)

[0110] 10 parts of the initiator polymer-1 and 1.5 parts of a curing agent (isophoronediamine (IPDA)) were mixed, and propylene glycol monomethyl ether acetate (PGMEA) was added and mixed so that the solid content became 25%, thereby obtaining a coating liquid (COT-1).

[0111] (Manufacturing example 2: COT-2)

[0112] A coating liquid (COT-2) was obtained in the same manner as in Production Example 1 except that 10 parts of initiator polymer-2 and 0.2 parts of curing agent (IPDA) were used.

[0113] (Production Example 3: COT-3)

[0114] 10 parts of the initiator polymer-3 were dissolved in NMP so that the solid content became 25%, thereby obtaining a coating liquid (COT-3).

[0115] (Production Example 4: COT-4)

[0116] 10 parts of initiator polymer-4 and 3.5 parts of a curing agent (biuret type polyisocyanate, trade name "DURANATE 24A-100", manufactured by Asahi Kasei Corporation) were mixed, and diethylene glycol dimethyl ether (DMDG) was added and mixed so that the solid content became 25% to obtain a coating liquid (COT-4).

[0117] (Comparative Production Example 1: COT-C-1)

[0118] A coating liquid (COT-C-1) was obtained in the same manner as in Production Example 4 except that the comparative initiator polymer-1 was used instead of the initiator polymer-4.

[0119] <Production of a substrate for providing a polymer layer (iii) (1)>

[0120] (Production Example 5: SUB-1)

[0121] A SUS plate that has been surface activated by washing and UV ozone is prepared as a substrate. COT-1 is applied to the surface of the prepared substrate using a spin coater at 2,000 rpm for 30 seconds. After being placed in an oven at 80°C and dried for 10 minutes, it is placed in an oven at 100°C and heated for 120 minutes to cure it, thereby forming a polymer layer (iii) and obtaining a substrate to which the polymer layer (iii) is applied, namely SUB-1. The film thickness of the polymer layer (iii) measured by spectroscopic ellipsometer (trade name "VASE", manufactured by JA Woollam) is 1,192 nm. After the obtained SUB-1 is immersed in THF and ultrasonically cleaned for 5 minutes, the film thickness of the polymer layer (iii) is measured again. As a result, the film thickness of the polymer layer (iii) is almost unchanged compared to that before cleaning, and it can be confirmed that a fully cured polymer layer (iii) has been formed.

[0122] (Manufacturing Examples 6 to 8, Comparative Manufacturing Example 2: SUB-2 to 4, SUB-C-1]

[0123] Substrates to which the polymer layer (iii) was provided, namely SUB-2 to 4 and SUB-C-1, were obtained in the same manner as in Production Example 5 except that the conditions were set as shown in the lower part of Table 1.

[0124] Table 1

[0125]

[0126] <Manufacturing of coating liquid (2)>

[0127] (Production Example 9: COT-5)

[0128] 10 parts of bisphenol A epoxy resin (trade name "jER-1001", manufactured by Mitsubishi Chemical Corporation) and 1.5 parts of a curing agent (4,4'-diaminodiphenylmethane (MDA)) were mixed, and PGMEA was added and mixed so that the solid content was 25% to obtain a coating liquid (COT-5).

[0129] (Production Example 10: COT-6)

[0130] 5.5 parts of BIS-AP-AF and 35.1 parts of DMAc were mixed and stirred at room temperature to dissolve, 3.3 parts of PMDA were added little by little to dissolve, and then stirred at room temperature for 12 hours to obtain a coating liquid (COT-6).

[0131] (Production Example 11: COT-7)

[0132] 16 parts of a hydroxyl-containing polymer and 2.1 parts of a curing agent (biuret-type polyisocyanate, trade name "DURANATE 24A-100", manufactured by Asahi Kasei Corporation) were mixed, and DMDG was added and mixed so that the solid content became 25% to obtain a coating liquid (COT-7).

[0133] <Production of a substrate for providing a polymer layer (iii) (2)>

[0134] (Production Example 12: SUB-5)

[0135] Prepare a glass plate that has been surface activated by washing and UV ozone as a substrate. Coat COT-5 on the surface of the prepared substrate using a spin coater at 2,000 rpm for 30 seconds. After being placed in an oven at 80°C and dried for 10 minutes, it was placed in an oven at 150°C and heated for 60 minutes to solidify it to form a polymer layer, thereby obtaining a substrate to which a polymer layer is imparted. The film thickness of the polymer layer is 1,219 nm. After immersing the obtained substrate to which a polymer layer is imparted in THF and ultrasonically cleaning it for 5 minutes, the film thickness of the polymer layer was measured again. As a result, the film thickness of the polymer layer remained almost unchanged compared to before cleaning, and it was confirmed that a fully cured polymer layer was formed.

[0136] 157 parts of THF, 5.9 parts of pyridine and 11.5 parts of BiBB were placed in a glass container. The substrate to which the polymer layer was to be applied was immersed, and the upper part of the container was covered with paraffin film. After standing at room temperature for 1 hour, the substrate was thoroughly washed with THF and then air-dried to obtain the substrate to which the polymer layer (iii), namely SUB-5, was applied. The film thickness of the polymer layer (iii) was 1,219 nm. When the surface of the obtained substrate (polymer layer (iii)) was analyzed by ATR-IR at 1,735 cm -1 Absorption derived from ester bonds was observed near the surface of the polymer layer. In addition, by combustion IC analysis using an ion chromatography (IC) device (trade name "IC-2001", manufactured by Tosoh Corporation, column: SI-354D (manufactured by Akihabara Scientific Co., Ltd.), developing solvent: 3 mmol / L sodium carbonate aqueous solution), it was confirmed that the amount of Br was 41 mg / g. Based on the above analysis results, it can be confirmed that the polymer layer (iii) is formed by an initiating group polymer into which the functional group represented by the general formula (1) is introduced. It should be noted that in the initiating group polymer, the content of the functional group represented by the general formula (1) is 1.3 mmol / g.

[0137] (Production Examples 13, 14: SUB-6, 7)

[0138] The same operation as in the above-mentioned manufacturing example 12 was performed except that the conditions shown in the lower part of Table 2 were set to obtain substrates for imparting polymer layer (iii), namely SUB-6 and 7. In the initiator polymer forming the polymer layer (iii) of SUB-6, the content of the functional group represented by the general formula (1) was 0.8 mmol / g. In addition, in the initiator polymer forming the polymer layer (iii) of SUB-7, the content of the functional group represented by the general formula (1) was 0.5 mmol / g.

[0139] Table 2

[0140]

[0141] <Manufacturing of a substrate having a surface-treated film>

[0142] (Example 1: SUB-8)

[0143] Under an argon atmosphere, 0.00098 parts of ethyl 2-bromoisobutyrate (EBiB), 0.080 parts of copper (II) bromide (CuBr2), 0.46 parts of copper (I) bromide (CuBr), 3.2 parts of 4,4'-dinonyl-2,2'-bipyridine (dNbpy), 100.1 parts of methyl methacrylate (MMA) and 103.9 parts of anisole were put into a flask and stirred to prepare a polymerization solution. The substrate SUB-1 to which the polymer layer (iii) is given is put into a screw-mouth container made of PTFE, and the container is filled with the prepared polymerization solution and covered, and the lid is wrapped with paraffin film. The container is placed in an aluminum laminate bag and heat-sealed while degassing. The container together with the aluminum laminate bag was placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation) containing water as a pressurized medium, and while heating to 60°C, pressurized to 400 MPa and polymerized for 4 hours. A highly viscous solution containing a polymer was generated in the high-pressure device, and a portion of the polymer was sampled and measured to have an Mn of 2,540,000 and a PDI of 1.10. The substrate removed from the container was thoroughly cleaned with THF. The film thickness of the polymer layer (ii) measured by spectroscopic ellipsometry was 680 nm, and it was confirmed that a surface-treated film having a laminated structure in which a polymer layer (ii) was laminated on a polymer layer (i) was formed on the surface of the SUS plate.

[0144] The obtained substrate provided with a surface-treated film was designated as SUB-8.

[0145] (Example 2: SUB-9)

[0146] Under an argon atmosphere, 0.00054 parts of EBiB, 55.5 parts of KJCMPA, 55.1 parts of MMA and 0.41 parts of tetrabutylammonium iodide (TBAI) were added to a flask and stirred to prepare a polymerization solution. The substrate SUB-2 to which the polymer layer (iii) was given was added to a screw-mouth container made of PTFE, and the container was filled with the prepared polymerization solution and covered, and the lid was wrapped with paraffin film. The container was placed in an aluminum laminate bag and heat-sealed while degassing. The container and the aluminum laminate bag were placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation) containing water as a pressurized medium, and while heating to 75°C, pressurized to 400MPa and polymerized for 4 hours. A highly viscous solution containing a polymer was generated in the high-pressure device, and a portion of the polymer was sampled and measured to have an Mn of 2,111,000 and a PDI of 1.50. The substrate removed from the container was thoroughly washed with THF. The film thickness of the polymer layer (ii) measured by spectroscopic ellipsometry was 603 nm, confirming that a surface-treated film having a laminated structure in which a polymer layer (ii) was laminated on a polymer layer (i) was formed on the surface of the SUS plate. The substrate to which the surface-treated film was applied was set to SUB-9.

[0147] (Examples 3 to 7, Comparative Example 1: SUB-10 to 14, SUB-C-2)

[0148] The same operation as in Example 1 or 2 was performed except that the substrate and monomer for providing the polymer layer (iii) of the type shown in Table 3 were used to obtain the substrate for providing the surface treatment film, namely SUB-10 to 14 and SUB-C-2. The details of the obtained substrate for providing the surface treatment film are shown in Table 3. It should be noted that the meanings of the abbreviations in Table 3 are shown below.

[0149] ·LMA: Lauryl Methacrylate

[0150] PEGMA: polyethylene glycol monomethyl ether of methacrylate (molecular weight 200)

[0151] Table 3

[0152]

[0153] <Evaluation>

[0154] (Rating (1): SUB-8)

[0155] The SUB-8 obtained in Example 1 was immersed in toluene overnight to swell the surface treated film. Using a friction tester (trade name "Heidon Friction Tester 14", manufactured by Shinto Scientific Co., Ltd.), a 1,000-reciprocating ball indenter sliding test was performed under the conditions of a load of 1,000 g, an amplitude of 30 mm, and a sliding speed of 200 mm / min. As a result of data analysis, the friction coefficient was 0.0015, and there was no change in the friction coefficient after 1,000 reciprocations. When a laser microscope was used to observe the surface after the sliding test, no wear was confirmed. In summary, it can be confirmed that SUB-8 has low friction and high durability.

[0156] (Rating (2): SUB-11)

[0157] The SUB-11 obtained in Example 4 was subjected to a sliding test in the same manner as in the above evaluation (1), except that it was immersed in diisotridecyl adipate instead of toluene. As a result, the friction coefficient was 0.0010, and the friction coefficient did not change even after 1,000 reciprocating movements. When the surface after the sliding test was observed using a laser microscope, no wear was confirmed. In summary, it can be confirmed that SUB-11 has low friction and high durability.

[0158] (Evaluation (3): SUB-C-2)

[0159] The same operation as the above evaluation (1) was performed on the SUB-C-2 obtained in Comparative Example 1. As a result, the initial friction coefficient was 0.09, but after about 10 reciprocating movements, the friction coefficient slowly increased, and the friction coefficient reached 0.2 after 100 reciprocating movements. When the surface after the sliding test was observed using a laser microscope, wear marks were observed. SUB-C-2 is a substrate for imparting a surface treatment film, which is manufactured using a substrate having a polymer layer (iii) formed by a polymer having a small amount of functional groups introduced as shown in the general formula (1). Therefore, the polymer density of the formed polymer layer (ii) is low, and a thick polymer brush cannot be formed. Therefore, it can be considered that: the friction coefficient is high, high lubricity is not shown, durability is lacking, and it is easy to wear.

[0160] Industrial Applicability

[0161] The surface treatment film of the present invention is useful as a material provided on a sliding surface of a sliding member constituting various equipment belonging to automobiles, medical equipment, automatic devices, aviation / space industries, energy, battery components, precision equipment, etc.

Claims

1. A surface treatment film provided on the surface of a substrate, The surface treatment film has a laminated structure including a polymer layer (i) and a polymer layer (ii), wherein the polymer layer (i) is arranged on the surface side of the substrate, and the polymer layer (ii) is arranged on the polymer layer (i). The polymer layer (i) contains a first polymer, the first polymer is derived from a polymer containing a polymerization initiating group, the polymer containing a polymerization initiating group has a functional group represented by the following general formula (1) in a side chain that functions as a polymerization initiating group, and is selected from at least one of the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin, and in the polymer containing a polymerization initiating group, the content of the functional group represented by the general formula (1) is 0.5 mmol / g or more, The film thickness of the polymer layer (ii) is 200 nm or more, The polymer layer (ii) contains a second polymer, the second polymer comprises a structural unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a (meth)acrylate monomer, and a (meth)acrylamide monomer, and the chain is extended using a functional group represented by the following general formula (1) as a polymerization initiation point, In the general formula (1), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; Y represents O or NH; and * represents a bonding position.

2. The surface treatment film according to claim 1, wherein The polymer layer (i) has a three-dimensional network structure.

3. The surface treatment film according to claim 1 or 2, wherein: The polymer layer (i) has a thickness of 500 nm or more.

4. The surface treatment film according to claim 1 or 2, wherein: The polymer containing a polymerization initiating group has a functional group represented by the general formula (1) in a side chain and is at least one selected from the group consisting of polyester, polyurethane, polyimide and epoxy resin.

5. The surface treatment film according to claim 1 or 2, wherein: The polymer layer (ii) contains a solvent and is swollen. 6 . The surface treatment film according to claim 1 , which is provided on the surface of the substrate, and the substrate does not include a porous substrate.

7. The surface treatment film according to claim 1 or 2, wherein: The polystyrene-equivalent number average molecular weight of the second polymer measured by gel permeation chromatography is 100,000 or more.

8. A method for producing a surface treatment film, which is the method for producing a surface treatment film according to any one of claims 1 to 7, comprising the following steps: A step of forming a polymer layer (iii) on the surface of the substrate, wherein the polymer layer (iii) contains the polymer containing a polymerization initiating group; and A process of polymerizing one or more monomers selected from the group consisting of aromatic vinyl monomers, (meth)acrylate monomers and (meth)acrylamide monomers in the presence of the polymer layer (iii) to form a stacked structure comprising the polymer layer (i) and the polymer layer (ii), wherein the polymer layer (i) contains the first polymer derived from the polymer containing a polymerization initiating group, and the polymer layer (ii) is arranged on the polymer layer (i) and contains the second polymer containing a structural unit derived from the monomer.

9. The method for producing a surface treatment film according to claim 8, wherein: The polymer containing a polymerization initiating group is coated on the surface of the substrate to form the polymer layer (iii).

10. The method for producing a surface treatment film according to claim 8, wherein: After coating the surface of the substrate with at least one polymer having a hydroxyl group or an amino group in a side chain and selected from the group consisting of polyester, polyurethane, polyamide, polyimide and epoxy resin, the polymer layer (iii) is formed by reacting the polymer with the compound represented by the following general formula (2). In the general formula (2), R1 represents a hydrogen atom, a methyl group, an ethyl group, a phenyl group or an acyl group; R2 represents a methyl group, an ethyl group or an acyl group; X represents a chlorine atom, a bromine atom or an iodine atom; and Z represents a chlorine atom or a bromine atom.

11. The method for producing a surface treatment film according to any one of claims 8 to 10, wherein: In the presence of the polymer layer (iii), the monomer is subjected to surface initiated living free radical polymerization.

12. The method for producing a surface treatment film according to any one of claims 8 to 10, wherein: The monomers are polymerized under a pressure condition of 10 to 1,000 MPa.

13. The method for producing a surface treatment film according to any one of claims 8 to 10, wherein: The monomers are polymerized under a pressure condition of 100 to 1,000 MPa.

14. An article having: substrate; and The surface treatment film according to any one of claims 1 to 7 provided on the surface of the substrate.

Citation Information

Patent Citations

  • Surface-hydrophilic polyolefin molding and method for producing the same

    JP2008133434A

  • Surface-decorated base material and polymer-coated base material

    JP2010261001A

  • Functionalized thin film polyamide membranes

    CN102112214A

  • Novel biological pollution-resistant polyamide reverse osmosis composite membrane and preparation method thereof

    CN105833749A